ANALISIS FLYPAPER EFFECT PADA BELANJA DAERAH DAN IMPLIKASINYA TERHADAP KEMANDIRIAN KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Nurdiah Anjas Kesuma; Kartika Rachma Sari; Darul Amri; Masnoni Masnoni (Politeknik Negeri Sriwijaya, 2022)
This study aims to examine the effect of Regional Original Income (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) on Regional Expenditures, see if there is a Flypaper Effect on Regional Expenditures, and its implications for the Level of Regency/City Regional Financial Independence. in South Sumatra Province in 2015-2019. The data used in this study is the Budget Realization Report (LRA) in the District / City Government Financial Statements of South Sumatra Province. The population of this research is LRA in 17 regencies/cities in South Sumatra Province for the 2015-2019 Fiscal Year using the saturated sampling method and 85 units of observation. The results show that PAD has a significant effect on Regional Expenditures, DAU have a significant effect on Regional Expenditures, DAK have no and no significant effect on Regional Expenditures, PAD, DAU, and DAK simultaneously have an effect on Regional Expenditures, PAD, DAU, DAK, and Regional Expenditures affect the Level of Regional Financial Independence, and the occurrence of the Flypaper Effect on Regional Expenditures in the Regency/City of South Sumatra Province